Pharmacokinetics and Safety of Intravenous Murepavadin Infusion in Healthy Adult Subjects Administered Single and Multiple Ascending Doses - Wach, Achim; Dembowsky, Klaus; Dale, Glenn E. (Antimicrobial agents and chemotherapy, 2018)
Murepavadin is the first in class of the outer membrane protein-targeting antibiotics (OMPTA) and a pathogen-specific peptidomimetic antibacterial with a novel, nonlytic mechanism of action targeting Pseudomonas aeruginosa . Murepavadin is being developed for the treatment of hospital-acquired bacterial pneumonia (HABP) and ventilator-associated bacterial pneumonia (VABP). The pharmacokinetics (PK) and safety of single and multiple doses of murepavadin were investigated in healthy male subjects. Part A of the study was a double-blind, randomized, placebo-controlled, single-ascending-dose investigation in 10 sequential cohorts where each cohort comprised 6 healthy male subjects; 4 subjects were randomized to murepavadin, and 2 subjects were randomized to placebo. Part B was a double-blind, randomized, placebo-controlled, multiple-ascending-dose investigation in 3 sequential cohorts. After a single dose of murepavadin, the geometric mean half-life (2.52 to 5.30 h), the total clearance (80.1 to 114 ml/h/kg), and the volume of distribution (415 to 724 ml/kg) were consistent across dose levels. The pharmacokinetics of the dosing regimens evaluated were dose proportional and linear. Murepavadin was well tolerated, adverse events were transient and generally mild, and no dose-limiting toxicity was identified.